CD4 binding site broadly neutralizing antibody selection of HIV-1 escape mutants - Dreja, Hanna (J Gen Virol, 2015)
All human immunodeficiency virus type-1 (HIV-1) viruses use CD4 to enter cells. Consequently, the viral envelope CD4-binding site (CD4bs) is relatively conserved, making it a logical neutralizing antibody target. It is important to understand how CD4-binding site variation allows for escape from neutralizing antibodies. Alanine scanning mutagenesis identifies residues in antigenic sites, whereas escape mutant selection identifies viable mutants. We selected HIV-1 to escape CD4bs neutralizing mAbs b12, A12 and HJ16. Viruses that escape from A12 and b12 remained susceptible to HJ16, VRC01 and J3, whilst six different viruses that escape HJ16 remained sensitive to A12, b12 and J3. In contrast, their sensitivity to VRC01 was variable. Triple HJ16/A12/b12-resistant virus proved that HIV-1 could escape multiple broadly neutralizing monoclonal antibodies, but still retain sensitivity to VRC01 and the llama-derived J3 nanobody. This antigenic variability may reflect that occurring in circulating viruses, so studies like this can predict immunologically relevant antigenic forms of the CD4bs for inclusion in HIV-1 vaccines.